Techno-economic modelling of low-voltage networks: A concept to determine the grid investment required in Germany and the implications for grid utilisation fees - Simon Marwitz; Rainer Elsland (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
The increasing deployment of decentralised rooftop photovoltaic systems (PV systems) and the expected future diffusion of plug-in electric vehicles (PEVs) can have a major influence on the need to expand low-voltage networks in the near future. The associated grid investments are refinanced via grid utilisation fees (GUF). Some of the GUF are passed on from higher to lower voltage lev-els. At the same time, decentralised electricity generation from PV systems is currently exempt from paying GUF in Germany. This study determines the grid investment required based on the example of a low-voltage network in a suburb and the underlying change in electricity demand used to refinance the grid in-vestment. A newly developed modelling concept is introduced to do so. The analysis focuses on the German household sector for the year 2030. Key find-ings from the analysis are that the future penetration of PV systems and the charging capacity of PEVs will have a considerable influence on maximum grid loads and the associated investment requirements. The required grid invest-ment mainly concerns additional lines or (adjustable) local grid transformers. Furthermore, the analysis shows a direct correlation between the self-consumption of decentrally generated power, the increased electricity demand due to PEVs and the required grid investment. This shows that additional grid investment is required from an average penetration rate of 0.5 kW PEV inverter power output per person and 1 kWp installed PV capacity per person in the lo-cal network area. At the same time, GUF can be reduced due to the increase in electricity demand by PEVs. Correspondingly, PV systems reduce the amount of power withdrawn from the grid, which means the specific GUF could increase by up to 2.1 eurocent per kWh by 2030 under the current surcharge mecha-nism. Households with an electric vehicle but without a photovoltaic system contribute roughly four times as much to refinancing the electric grids as com-parable households without an electric vehicle but with a photovoltaic system do.
urn:nbn:de:0011-n-5153021
Keywords: 330; electric vehicle (PEV); rooftop photovoltaic system